Pengaruh Komposisi Tepung Jewawut (Setaria Italica) dan Tepung Kacang Kedelai (Glycine Max L.) terhadap Serat Pangan, Proksimat, dan Sifat Organoleptik Sereal untuk Diabetes Melitus: The Effect of Millet (Setaria Italica) Flour and Soybean (Glycine Max L.) Flour Composition on Dietary Fiber, Proximate Content, and Organoleptic Properties of Cereal for Diabetes Mellitus - Syifa Salsa Maharani; A'immatul Fauziyah; Nanang Nasrulloh (Amerta Nutrition, 2025)
Background: Based on International Diabetes Federation (2025), there are 20.4 million individuals in Indonesia (aged 20–79 years) suffering from diabetes mellitus as of 2024. Managing the amount and type of food consumption is required as a corrective measure to prevent complications. Dietary fiber and protein have been shown to be effective in controlling glucose and increasing satiety. Objectives: To analyze the effects of millet flour and soybean flour composition on dietary fiber, proximate content, and organoleptic properties of cereal intended for individuals with diabetes mellitus. Methods: This experimental study used a Completely Randomized Design (CRD) with 3 treatment levels based on millet flour and soybean flour, namely 100%:0% (F1), 75%:25% (F2), and 50%:50% (F3), with two replications for each. Analysis of chemical content employed one-way ANOVA, followed by Duncan test if significant differences were found. Furthermore, organoleptic properties were analyzed by Kruskal Wallis test and Mann-Whitney test to identify significant differences among formulas. The best formulation was selected using the De Garmo method. Results: Chemical test results showed significant differences for ash, protein, fat, carbohydrate, and dietary fiber (p-value<0.05) among formulas. Hedonic test showed significant differences (p-value<0.05) in texture and cereal taste acceptance in each formula. The best formula was F3, which contained 4.91% water, 2.38% ash, 5.66% dietary fiber, 17.48% protein, 20.58% fat, and 54.76% carbohydrate. Conclusions: The proportion of millet flour and soybean flour significantly increased ash, protein, fat, and dietary fiber content; significantly decreased carbohydrate content; and significantly influenced texture and taste acceptance, but did not influence water content, color, and aroma acceptance of cereals.